Determinants of Consumer Perceptions of the Ethics of Online Retailers: An Investigation Using Confirmatory Factor Analysis - Saptarshi Bhattacharya; Rajendra Prasad Sharma
Though the online retailing ethics literature has been growing steadily, no research has attempted to examine the myriad aspects and concerns about the online retailers$1 (Bunethical practices and behaviours. The study aims to extend the research and re-validate the consumer perception of ethics of online retailers (CPEOR) scale in the Indian context. The methodology involves an exploratory factor analysis on a sample of 261 online shopper responses on a 7-point Likert scale. The obtained scale was then validated on a new sample of 416 users using confirmatory factor analysis. The research identifies and validates 10 factors that influence CPEOR, that is, privacy, security, non-deception, fulfilment, customer service, service recovery, fairness concerns, environmental concerns, corporate social responsibility and ethical policies. The study offers valuable insights to the managers and researchers. The study offers best practices in the different dimensions of CPEOR along with future research directions. The study provides unified and comprehensive insights on CPEOR by examining all possible dimensions of CPEOR.s